Should we build a garden city? Politicising knowledge and concepts in planning policy and practice. Issue 2 (March 2016) - Biddulph, Mike
Abstract : Governments can appropriate well understood planning concepts without fully acknowledging their heritage, meaning and implications. The English government's reference to garden villages as a model for future residential developments is considered a good example. The article highlights the government's changing rhetoric in the promotion of similar, but evolving forms of neighbourhood development. It is argued that we need to look beyond this rhetoric, and maintain a clear concern for realising developments which conform to established urban design principles and thinking.